2015
DOI: 10.18806/tesl.v31i0.1188
|View full text |Cite
|
Sign up to set email alerts
|

A Typology of Tasks for Mobile-Assisted Language Learning: Recommendations from a Small-Scale Needs Analysis

Abstract: In response to the research priorities of members of TESOL (Teachers of English to Speakers of Other Languages), this study investigated language learners' realworld tasks in mobile-assisted language learning (MALL) En réponse aux priorités de recherche des membres de TESOL (enseignement de l'anglais à des apprenants étrangers), cette étude a porté sur les tâches réelles dans le contexte de l'apprentissage mobile des langues pour ensuite éclairer le développement de tâches pédagogiques pour l'anglais académi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…The evidence of this phenomenon is the growing body of research in English as a second or an additional foreign language. The foci of these researchers have been on policy issues, best practices, teacher education, and learner needs (Oliver, Grote, Rochecoute, & Exell, 2013;Park & Slater, 2014;Safford & Costley, 2008).…”
Section: English Learning In Native English-speaking Countriesmentioning
confidence: 99%
“…The evidence of this phenomenon is the growing body of research in English as a second or an additional foreign language. The foci of these researchers have been on policy issues, best practices, teacher education, and learner needs (Oliver, Grote, Rochecoute, & Exell, 2013;Park & Slater, 2014;Safford & Costley, 2008).…”
Section: English Learning In Native English-speaking Countriesmentioning
confidence: 99%
“…Most studies in the United States have addressed adult learners and college students rather than elementary or secondary students (e.g., D. Kim, Rueckert, Kim, & Seo, 2013; Li & Hegelheimer, 2013; Nisbet & Austin, 2013; Park & Slater, 2014). In terms of college students, researchers found that teachers of English language used technology less often than students in their daily lives (Park & Slater, 2014) and concluded that this may affect how well teachers integrate mobile technologies into the classroom and curriculum. In this study, 60% of ELL students at a midwestern university had used mobile technologies in their classes and learning experiences, whereas only 15% of graduate students who taught them had done so.…”
Section: Findings From Previous Mobile Device Studiesmentioning
confidence: 99%
“…Researchers have used them as pedagogical tools in order to expose learners to authentic communication situations and tasks that they will need to accomplish using the target language. In fact, several studies have pointed out that as educational tools, applications on mobile devices "can provide language learners with real-world opportunities to negotiate meaning and to engage with comprehensible input and output" [20].…”
Section: Educational Benefits and Drawbacks Of Mallmentioning
confidence: 99%
“…Concerning the nature of studies, in regard to the benefits and drawbacks of MALL, they can be classified in two types: implementation studies and review studies. Burston's (2013) [20] annotated bibliography is the most completed review study which provides a comprehensive historical background of MALL applications (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012).…”
Section: Educational Benefits and Drawbacks Of Mallmentioning
confidence: 99%
See 1 more Smart Citation